2014
DOI: 10.1155/2014/230835
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Role of Globular Adiponectin in Treatment with HFD/STZ Induced T2DM Combined with NAFLD Rats

Abstract: Aims. To evaluate the effects of globular adiponectin (gAd) on treatment of type 2 diabetic rats combined with NAFLD. Materials and Methods. Twenty-one male wistar rats were fed with normal diet (7 rats) or high fat diet (HFD) (14 rats) for 4 weeks, and then HFD-fed rats were injected with streptozotocin (STZ) to induce type 2 diabetes mellitus (T2DM). Half of T2DM rats were randomly injected with gAd intraperitoneally for 7 days. The expressions of adiponectin receptors (adipoR1/R2) in liver and skeletal musc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…HFD/STZ‐induced T2DM rats were carried out by the method of Ma et al. (2014) with slight modifications. After 1‐week adaptation, they were fed an HFD (60% calories from fat) for 4 weeks.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…HFD/STZ‐induced T2DM rats were carried out by the method of Ma et al. (2014) with slight modifications. After 1‐week adaptation, they were fed an HFD (60% calories from fat) for 4 weeks.…”
Section: Methodsmentioning
confidence: 99%
“…The rats were maintained under standard laboratory conditions at a temperature of 23 ± 1°C and a 12-hr light/12-hr dark cycle, with free access to food and water for the duration of the study. HFD/STZ-induced T2DM rats were carried out by the method of Ma et al (2014) with slight modifications. After 1-week adaptation, they were fed an HFD (60% calories from fat) for 4 weeks.…”
Section: Animals and Dietsmentioning
confidence: 99%
“…The test monkeys were housed in single cage (80 × 80 × 100 cm) in experimental animal house with 3 meals, free to drink pure water and sufficient illuminance (12 h/day), temperature (20 °) and moisture (40 %). The animals were in the T2DM group injected with STZ at a dosage administration of 35 mg per kg of body weight by intraperitoneal injection as soon as hyperlipidemia and hyperinsulinemia symptom appeared in both of high-sucrose/high-fat group and T2DM group [20][21][22].…”
mentioning
confidence: 99%
“…In addition, a meta-analysis based on five large-scale clinical trials revealed that the levels of FBG and TG were significantly reduced in patients with T2DM following treatment with fluoxetine hydrochloride compared with a placebo ( 9 , 10 ); however, the effects of fluoxetine on lipid metabolism and the underlying mechanisms remain unknown. In the present study, STZ-induced T2DM rats were used to mimic the metabolic characteristics of T2DM as reported previously ( 30 ); the effects of fluoxetine on glucose and lipid metabolism were investigated ( 31 ). Additionally, the levels of FBG and random glucose were significantly decreased in STZ-induced T2DM rats following treatment with fluoxetine hydrochloride in the present study, indicating that fluoxetine may reduce hyperglycemia and increase insulin sensitivity; the molecular mechanisms may be associated with muscle glycogen synthesis ( 32 ).…”
Section: Discussionmentioning
confidence: 99%